Jumlah Kepala Sekolah Dan Guru Menurut Kelompok Umur Provinsi Bengkulu, Nusa Tenggara Barat, Papua Pegunungan, Dan Papua Selatan - Riyad Firdaus, Muhammad; Wahyu Santoso, Agung; Muhammad Ilham, Ghatfani; Santoso, Rahmat; Rosyani, PE (CV. Shofanah Media Berkah, 2024)
This study aims to analyze the number of principals and teachers based on age groups in four provinces in Indonesia, namely Bengkulu, West Nusa Tenggara (NTB), Papua Pegunungan, and South Papua. The data used includes the age distribution of educators, which plays an important role in understanding the dynamics of the teaching staff and education policies at the local level. By looking at the distribution of principals and teachers in certain age ranges, this study provides an overview of the demographic conditions of educators that can influence recruitment, training, and professional development strategies in each province. The findings show significant variations in age distribution between provinces, reflecting specific needs in improving the competence and regeneration of educators in each region. This abstraction leads to policy implications in the education sector, especially in ensuring the regeneration and quality of educators to support improving the quality of education.